2017
DOI: 10.3139/146.111578
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural effects of isothermal aging on a doped SAC solder alloy

Abstract: An Sn–Ag–Cu based solder alloy, including Ni, Bi and Sb additives, is investigated in this study under isothermal aging conditions. Shear creep tests are conducted on different aged solder joints with copper substrate, giving the creep resistance evolution with aging time. Microscopy analyses reveal the limited growth of the Cu-rich intermetallic layer due to the Ni content and allow for determination of the time-dependent growth of the Sn-rich intermetallic layer. The aged specimens also exhibit a partial dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Concerning the element Bi, it was found in the parent tin phases in the form of small particles, which provides solid solution strengthening to the alloy 11 . In our previous studies, 11,18,19 it was reported that the phases work to strengthen the InnoLot solder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning the element Bi, it was found in the parent tin phases in the form of small particles, which provides solid solution strengthening to the alloy 11 . In our previous studies, 11,18,19 it was reported that the phases work to strengthen the InnoLot solder.…”
Section: Methodsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Furthermore, in automotive industry particularly, a novel lead-free solder, namely, InnoLot, has been created based on SAC387 solder with three small supplements of bismuth (Bi), antimony (Sb) and nickel (Ni). [17][18][19][20] The beneficial effects of these elements addition to tin-silver-copper (SAC) solder materials have been showed in previous studies. 8,15,16 Compared with conventional SAC solders, the InnoLot solder is characterized by microstructural refinement, solution strengthening and better toughness due to IMCs layers formed with Ni, Bi and Sb additions.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The strength of the bulk material appeared to be the weakest. The Mn precipitates caused grain refinement of β-tin grains inside the solder bulk as reported in the literature [ 20 , 21 ]. However, the finer grain structure did not necessarily yield a higher shear force.…”
Section: Resultsmentioning
confidence: 72%
“…They showed that Zn refined the grain structure of the solder joints and yielded less dendritic precipitation of Ag 3 Sn intermetallic compounds. Benabou et al analyzed the effect of adding nickel or antimony [ 20 ]. They revealed that these alloys under test suppress the growth of both Cu 6 Sn 5 and Cu 3 Sn intermetallic layers during high-temperature storage life tests.…”
Section: Introductionmentioning
confidence: 99%